PLANT GROWTH PROMOTION BY HALOTOLERANT ASPERGILLUS STRAINS - SUVARNA DNYANESHWAR PATIL; DR. ARPANA HEMRAJ JOBANPUTRA; DR. NAZIYA M. A. REHMAN; UMANATH GULABRAO FULPAGARE; MS. SAROJINI RANGARAO DESHMUKH; JAYASHRI VITHHAL BORASE (The Bioscan, 2025)
This study aimed to isolate, characterize, and evaluate halotolerant rhizospheric fungi from saline soils in Maharashtra, India, for their plant growth-promoting potential. Soil samples from four ecologically distinct sites—Lonar Lake, Mehrun Lake, Girgaon Coastal Region, and Surat Coastal Region—were analyzed for physicochemical properties (pH, EC, texture). Fungal isolates were obtained via serial dilution and plating on PDA with chloramphenicol, followed by halotolerance screening (2–14% NaCl). Among 20 isolates, 18 exhibited significant salt tolerance, with Aspergillus versicolor (F17) and Aspergillus proliferans (F20) showing the highest growth at 14% NaCl. Morphological, physiological, and molecular characterization (ITS sequencing) confirmed their identities. The isolates demonstrated multiple plant growth-promoting traits, including phosphate solubilization (F17: 11 cm halo; F20: 5 cm), zinc solubilization (F17: 12 cm halo; F20: 3 cm), ammonia production (F20: 7.8 μg/mL; F17: 7.2 μg/mL), nitrogen fixation (F20 > F17), EPS production (F17: 1300 μg/mL; F20: 1200 μg/mL), and IAA synthesis (F20: 7.8 μg/mL; F17: 7.2 μg/mL). In pot and seed germination assays, both fungi significantly enhanced wheat and maize growth compared to controls. F17-treated plants showed higher biomass (950 mg maize; 855 mg wheat fresh weight), while F20 improved root and shoot elongation (4.5 cm plant height in wheat). These findings highlight the potential of Aspergillus versicolor (F17) and Aspergillus proliferans (F20) as biofertilizers for saline agriculture due to their halotolerance, nutrient solubilization, and plant growth promotion.